Pesticide degrading natural multidrug resistance bacterial flora. (January 2018) - Rangasamy, Kirubakaran; Athiappan, Murugan; Devarajan, Natarajan; Samykannu, Gopinath; Parray, Javid A.; Aruljothi, K.N.; Shameem, Nowsheen; Alqarawi, Abdulaziz A.; Hashem, Abeer; Abd_Allah, Elsayed Fathi
Abstract: Multidrug-resistant (MDR) bacteria are a growing threat to humans across the world. Antibiotic resistance is a global problem that has developed through continuous antibiotic use, combinatorial antibiotic use, pesticide-antibiotic cross-resistance, and horizontal gene transfer, as well as various other modes. Pesticide-antibiotic cross-resistance and the subsequent expansion of drug-resistant bacteria are critically documented in this review, the primary focus of which is to assess the impact of indiscriminate pesticide use on the development of microbial communities with parallel pesticide and multidrug resistance. The consumption of pesticide-contaminated food products and the use of broad-spectrum antibiotics by humans and in livestock animals have favored the development of both antibiotic and pesticide-resistant bacterial flora via natural selection. Pesticide resistance mainly develops through defensive bacterial adaptations such as biofilm formation, induced mutations, and horizontal/vertical gene transfer through plasmids or transposons, as well as through the increased expression of certain hydrolytic enzymes. Pesticide resistance genes are always transferred as gene clusters, and they may also carry genes essential for antibiotic resistance. Moreover, for some induced mutations, the mutated active site of the affected enzyme may allow degradation of both pesticides and antibiotics, resulting in cross-resistance. A few studies have shown that the sub-lethal exposure of wild-type strains to herbicides induces antibiotic resistance. This review concludes that xenobiotic exposure leads to cross-resistance in wild microbial flora, which requires further study to develop therapeutic approaches to overcome the threats of MDR bacteria and superbugs. Highlights: The increase in pesticide usage leads to pesticide resistant strains. Pesticide resistant strains imparts antibiotic resistance to natural microbial flora. The pesticide resistant and antibiotic resistant microbial flora enters human through agricultural products or animals. The Hydrolase enzymes which degrade pesticides develop induced active site changes to resist antibiotics.